PENGARUH ARUS KAS OPERASI DAN LABA AKUNTANSI TERHADAP RETURN SAHAM - Rachmawati, Ria (Fakultas Ekonomi, Program Studi Akuntansi, 2016)
An investor in making an investment always expect a high stock return. Therefore investor should be able to assess which companies have good performance, so the return of it’s shares also high. Financial reports aspecially with regard to the information changes in operating cash flow and accounting earnings is one of the important information that can be used by investors to assess the company’s performance. This study aims to provide empirical evidence related to the influence of operating cash flow and profit accounting on stock returns. Population in this research is a food and beverage company in Bursa Efek Indonesia (BEI) year period 2013-2015 which amounted to 16 companies. Each company taken is a company that has a complete financial report data respectively during the period 2013-2015. The sample of this research is taken by using purposive sampling method because the selection of samples based on certain criteria. An analytical tool used in this research is multiple linier regression. Based on the result of this study, partially (t-Test) variable operating cash flow (X1) and the accounting profit (X2) had to significant effect on stock return. This is evidenced by the results of sig-t is greater than the 5% significance level (0,05). And simultaneously, the operating cash flow and accounting profit together no significant effect on stock returns